2018
DOI: 10.1007/s40430-018-1339-6
|View full text |Cite
|
Sign up to set email alerts
|

Thermal buckling of functionally graded triangular microplates

Abstract: The thermal buckling behavior of thin to moderately thick functionally graded isosceles triangular microplates with temperature-dependent material properties is investigated. The governing equations are derived based on the modified strain gradient theory (MSGT) in conjunction with the first-order shear deformation theory. The adjacent equilibrium criterion and Chebyshev-Ritz method are employed to derive the nonlinear thermal buckling eigenvalue equations, which are solved by a direct iterative method. The fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 51 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Using w d (x,t) = q(t) (x) in Eq. (37) and Galerkin discretization method, the following nonlinear ordinary differential equation is obtained:…”
Section: Micro-resonator On a Fixed Foundation (First Model)mentioning
confidence: 99%
See 1 more Smart Citation
“…Using w d (x,t) = q(t) (x) in Eq. (37) and Galerkin discretization method, the following nonlinear ordinary differential equation is obtained:…”
Section: Micro-resonator On a Fixed Foundation (First Model)mentioning
confidence: 99%
“…Furthermore, an indirect method for free vibration analysis, buckling, and bending of an FG micro-beam based on strain gradient theory has been proposed [36]. Other research attempts in the field of FGMs with micro-and nanoscales include thermal buckling of FG triangular micro-plates [37], free vibrations of sigmoid FG nano-beams using a modified couple stress theory with general shear deformation theory [38], and nonlinear dynamic stability of piezoelectric FG carbon nanotube-reinforced composite plates having geometric imperfection [39].…”
mentioning
confidence: 99%
“…The predicted answer for TVRPT satisfies the zero shear stress condition on the plate surfaces and does not need the shear correction factor. Moreover, TVRPT was used for modeling of thick FG plate [48]. According to the high efficiency of this theory, nano-plate, which needs higher accuracy in its results, was studied by TVRPT [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…An appropriate continuum-based model for a fluid-conveying nanostructure should be size-dependent since the static and dynamic behaviours of nanostructures are considerably influenced by size effects [2][3][4][5][6][7][8][9][10]. Several size-dependent models such as nonlocal [11][12][13][14][15][16], couple stress [17][18][19][20][21][22][23], and strain gradient [24,25] theories have been introduced for nanoscale structures. In the present analysis, a refined combination of the strain gradient and nonlocal models [26][27][28] is utilised since it has been reported that this continuum model is capable of better capturing size influences compared to the pure nonlocal model [29].…”
Section: Introductionmentioning
confidence: 99%